LEXICOGRAPHY OF THE POLISH LANGUAGE: HISTORICAL REVIEW - Lazarovych , O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The development of the lexicographical science in Poland coincides with the beginning of the development of the literary Polish language. Even though medieval dictionaries were not large from the point of view of the amount of words (in average from 2,5 to 4 thousand words), they were an important source of information on the vocabulary of the Polish language of that time, on the spiritual and material culture of the Polish nation. The article characterizes the development of the Polish lexicography from ancient times until the beginning of the XX-th century.